Knowledge Management in Agents of Things: A case study of smart classroom management - Ismail S.; Ahmad M.S. (2023)
Agent-based Knowledge Management (KM) systems have evolved through cross-fertilisation of knowledge from the domains of social sciences and information technology. Such evolution has paved the way for the development of agentmediated personal knowledge management (PKM) utilising intelligent software agents as the main system's workhorses. Furthering this development, this paper investigates an agentmediated KM system based on a novel PKM model, in a community of a university campus in Malaysia. The link between these two research domains is then visualised as a conceptual model to facilitate the development of the system. Three previously explored questionnaire surveys are analysed and triangulated in order to achieve the final conceptual models, which are illustrated as intelligent nodal entities to manifest the concept of Agents of Things (AoT). 2013 IEEE.